Understanding Behçet’s Disease in the Context of Innate Immunity Activation - Perazzio, Sandro F.; Andrade, Luis E. C.; de Souza, Alexandre W. S. (Frontiers in Immunology, 2020)
Behçet´s disease (BD) is a heterogeneous condition consisting of idiopathic systemic vasculitis affecting large and small blood vessels of different types (i.e., arteries, veins, or capillaries). The disease frequently occurs in young adults without gender predilection, differently from several other autoimmune conditions. This challenging illness has been recently proposed by some authors as an example of complex autoinflammatory syndrome. Although much remains unanswered about BD pathogenesis, recent understanding of some aspects of innate immunity have clarified a few issues (and raised others). HLA-B*51 represents the strongest genetic risk factor for BD to date, albeit several other HLA-independent loci have been also associated with the disease. The consistent hyper-reactivity against Streptococcus sanguinis antigens and alterations in oral and gut microbioma suggests that infectious agents may play an important role. Moreover, functional abnormalities of pattern recognition receptors, especially Toll-like receptors in monocytes, have been demonstrated in patients with BD and can be associated with the development of the disease. Neutrophil hyperactivity is one of the most consistent findings in BD pathogenesis, as demonstrated by exacerbated constitutive oxidative burst, chemotaxis and NET formation. However, some studies suggest that the phagocyte-activated status in BD is not primary to the disease itself, but rather restricted to a fraction of patients with severe disease activity, and probably secondary to activating soluble factors carried by serum/plasma from BD patients. Herein we review the state of the art on BD etiopathogenesis with special emphasis on the participation of the innate immune system.